A novel missense mutation p.S305R of EDA gene causes XLHED in a Chinese family. (November 2019) - Liu, Guannan; Wang, Xin; Qin, Man; Sun, Lisha; Zhu, Junxia
Highlights: A novel missense mutation S305R of EDA gene was found to cause X-linked hypohidrotic ectodermal dysplasia. This mutation located in the most conserved domain among TNF family ligands. This mutation resulted in insoluble mutant EDA1. Abstract: X-linked hypohidrotic ectodermal dysplasia (XLHED) can be characterized by hypohidrosis, sparse hair, hypodontia, and characteristic facial features and is usually caused by mutations of ectodysplasin A ( EDA ) gene located on the X chromosome. In this study, we examined a HED pedigree and studied the molecular genetics of the disease. A novel missense mutation was revealed by direct sequencing analysis in the EDA exon 7 (c.913 A > C, p.S305R). The impact of the mutation on the protein was studied in vitro in human embryonic kidney 293 T cells transfected with mutant or wild type forms of EDA . The mutant-type EDA1 protein showed impaired solubility comparing with wild-type EDA1. This novel missense EDA mutation was considered to be the cause of HED in the pedigree reported here. Our findings, combined with those reported elsewhere, provide an improved understanding of the pathogenic mechanism of HED as well as important information for a genetic diagnosis.